2010
DOI: 10.1211/jpp.62.05.0005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human liver microsomal CYP by nateglinide

Abstract: The possibility of drug-drug interactions involving nateglinide that might be attributable to CYP inhibition is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, the possibility of drug–drug interactions via CYP must be considered before using nateglinide. However, we have already reported that the possibility of drug–drug interactions due to inhibition of CYP by nateglinide is considered to be low, according to the results of in‐vitro experiments [4] . Moreover, the possibility of drug–drug interactions between nateglinide and other drugs was examined by in‐vitro experimentation using 18 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the possibility of drug–drug interactions via CYP must be considered before using nateglinide. However, we have already reported that the possibility of drug–drug interactions due to inhibition of CYP by nateglinide is considered to be low, according to the results of in‐vitro experiments [4] . Moreover, the possibility of drug–drug interactions between nateglinide and other drugs was examined by in‐vitro experimentation using 18 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, coadministration with amlodipine may decrease the metabolism of amlodipine, where a higher plasma concentration and a potential side effect such as hypotension are conceivable. Correspondingly, nateglinide is partly metabolized (30%) by CYP3A4 [ 207 ] and could be affected by inhibitors of CYP3A4. Furthermore, the majority of currently prescribed antineoplastic agents are metabolized by CYP3A4, for instance, docetaxel, erlotinib, imatinib, irinotecan, paclitaxel, and vinca alkaloids [ 208 ].…”
Section: Clinical Consequences Of Modulation Of Cytochrome P450 Anmentioning
confidence: 99%
“…Several in vitro and in vivo studies have reported the inhibitory effect of specific drugs on CYP2C19 and a few of them are CYP2C19 substrates ( Table 3). An oral hypoglycaemic agent nateglinide was also reported to have CYP2C19 inhibitory activity which may influence drug interactions in patients on nateglinide; nevertheless future studies are needed to investigate this in more detail [66]. Omeprazole inhibits its own metabolism and the same was hypothesized for clopidogrel [65].…”
Section: Cyp2c19 Induction and Inhibition By Xenobioticsmentioning
confidence: 99%